IMMUNOBIOLOGICAL PROPERTIES OF FOWLPOX VIRUS CULTURAL VARIANTS - K. Yu. Fedoseyev; M. S. Kukushkina; V. Yu. Kulakov; L. V. Malakhova (Ветеринария сегодня)
The paper presents experimental data of immunobiological properties of fowl pox virus cultural variants adapted in «F» CEF primary culture and «D» chicken embryo dermal primary cell culture. It was established that the strains retain dermatotropic phenotype manifested as local skin lesions in chicks, typical for Avipoxvirus family. They are also immunogenic and that is demonstrated as a protection after the vaccination with a homologous virus. The immunization doses were determined for both studied virus variants which ensured 95% protection of vaccinated birds. The doses were 14,6 и 6,97 ID50 for «F» and «D» correspondingly.